Interaction effect between blood selenium levels and stroke history on all-cause mortality: a retrospective cohort study of NHANES - Li, Yanli; Liu, Lanqun; Yang, Zufu; Xu, Jimin (Frontiers in Neurology, 2024)
The study aimed to investigate the interaction effect between blood selenium levels and stroke history on all-cause mortality.In this retrospective cohort study, data of participants were obtained from the National Health and Nutrition Examination Survey (NHANES) 2011-2018. The covariates were screened via the backward selection method in the weighted univariate and multivariate Cox regression models. Weighted univariate and multivariate Cox regression models were conducted to investigate the association of blood selenium, stroke history, with all-cause mortality. The results were expressed as hazard ratios (HRs) and 95% confidence intervals (CIs). The synergy index (SI) was used to assess the assistive interaction. The association further explored in different gender groups.In total, 8989 participants were included, of whom 861 (9.57%) died.Participants with blood selenium ≥192.96 ug/L was associated with lower odds of allcause mortality (HR=0.70, 95%CI: 0.58-0.84), while those with stroke history were associated with higher risk of all-cause mortality (HR=1.57, 95%CI: 1.15-2.16).Compared to participants with blood selenium ≥192.96 ug/L and non-stroke history, participants with both blood selenium <192.96 ug/L and stroke history had higher allcause mortality risk (HR=2.31, 95%CI: 1.62-3.29; SI=0.713, 95%CI: 0.533-0.952).Participants with blood selenium <192.96 ug/L, and those with stroke history were related to higher all-cause mortality risk (HR=1.61, 95%CI: 1.21-2.13). In males, the interaction effect of blood selenium and stroke history twice increased the chances of all-cause mortality (HR=2.27, 95%CI: 1.50-3.46; SI=0.651, 95%CI: 0.430-0.986).Blood selenium levels and stroke history on all-cause mortality 3 Conclusion: Blood selenium and stroke history have interaction effect on all-cause mortality. Increasing selenium-rich food or supplements intake, especially for individuals with stroke history, may improve the poor prognosis.